Comparison of efficacy, safety, and predictability of laser in situ keratomileusis using two laser suites - Meidani A (Dove Medical Press, 2016)
Alexandra Meidani,1–3 Chara Tzavara3 1Hypervision Laser Centre, 2Eye Day Clinic, 3Department of Hygiene, University of Athens Medical School, Centre for Health Services Research, Epidemiology and Medical Statistics, Athens, Greece Purpose: The main aim of this study was to compare the efficacy, safety, and predictability of femtosecond laser-assisted in situ keratomileusis performed by two different laser suites in the treatment of myopia for up to 6 months.Methods: In this two-site retrospective nonrandomized study, myopic eyes that underwent laser-assisted in situ keratomileusis using IntraLase FS 60 kHz formed group 1 and those using WaveLight FS200 femtosecond laser system formed group 2. Ablation was performed with Visx Star S4 IR and WaveLight EX500 Excimer lasers, respectively, in groups 1 and 2. Both groups were well matched for age, sex, and mean level of preoperative refractive spherical equivalent (MRSE). Uncorrected distance visual acuity, corrected distance visual acuity, and MRSE were evaluated preoperatively and at 1 week, 1 month, and 6 months after treatment.Results: Fifty-six eyes of 28 patients were included in the study. At 6-month follow-up postop, 78.6% of eyes in group 1 and 92.8% of eyes in group 2 achieved an uncorrected distance visual acuity of 20/20 or better (P=0.252). 35.7% and 50% in group 1 and group 2, respectively, gained one line (P=0.179). No eye lost lines of corrected distance visual acuity. Twenty-five eyes in group 1 (92.7%) and 27 eyes in group 2 (96.3%) had MRSE within ±0.5 D in the 6-month follow-up (P>0.999). The mean efficacy index at 6 months was similar in group 1 and group 2 (mean 1.10±0.12 [standard deviation] vs 1.10±0.1) (P=0.799). The mean safety index was similar in group 1 and group 2 (mean 1.10±0.10 [standard deviation] vs 1.10±0.09) (P=0.407).Conclusion: The outcomes were excellent between the two laser suites. There were no significant differences at 6-month follow-up postop between the two laser systems. Keywords: myopia, LASIK, IntraLase FS 60 kHz, WaveLight FS200, Visx Star S4 IR, WaveLight EX500